Editorial - Halilović, Haris (Kriminalističke teme, 2016)
Dear reader, In this English edition of the Criminal Justice Issues – the Journal of Criminal justice and Security we are introducing you two new scientific papers, one preliminary note and one review paper that discuss actual problems in the field of criminology of juvenile delinquency, criminal law and justice, social work and international law. The first of the mentioned papers is original scientific paper titled Does Law Self-Control Predict Juvenile Delinquency Among a Nationally Representative Sample of Bosnian Adolescents? Paper examines the robustness of Gottfredson and Hirschi’s (1990) general theory of crime by examining whether or not low self-control predicts juvenile delinquency among adolescents residing in Bosnia and Herzegovina. The next original scientific paper titled Organized Crime and Corruption Offences in the Final Verdicts of Bosnian Courts: Where is the link? Paper examines relations between organized crime and corruption in final verdicts of Bosnia and Herzegovina Court, Cantonal and Municipal Court in Sarajevo. Preliminary note titled as Analysis of the Existing Community - Level Child Protection Practice in Bosnia and Herzegovina is articulated around specific area of interest including system in place for the delivery of child protection services, related policies and frameworks, child protection education and resource management, data from research of the child protection, workforce key skills, knowledge, and interests. Finally, review paper titled International Law and Cyber Security discuss issues related to the application of the rules of international law and law of armed conflict to counter cyber threats. At the end, I would like to express my gratitude to Editorial Board members, authors and peer reviewers who have significantly contributed to the quality of this edition.